"It's hard work, believe me!": Active efforts to optimise housing by people who live with mental illness and access housing assistance. Issue 4 (29th November 2017) - Honey, Anne; Nugent, Alexandra; Hancock, Nicola; Scanlan, Justin
Abstract: Secure and appropriate housing is critical for the well‐being of people living with mental illness (consumers). Yet it is often difficult to achieve. Housing assistance is available, but is often difficult for consumers to access and negotiate. While the need for support is well‐recognised, little is known about the active part consumers play in finding and keeping appropriate accommodation. This paper addresses the research question: How do consumers who use housing assistance actively manage their housing situations? In‐depth interviews were conducted with 18 consumers who had used housing assistance within the past five years. These were analysed using constant comparative analysis, based on a grounded theory approach. Participants engaged in a range of activities to address six major concerns: working toward my home; following the rules to keep what I have; managing and improving my accommodation; working with housing services; living within my current situation; and finding and using supports. All participants described times when their mental health negatively affected their ability to do these activities. The findings highlight the need for housing services and mental health services to collaborate to develop policies and protocols that place reasonable demands on consumers and support their abilities to actively manage their housing situations.